One-stop procedure for persistent atrial fibrillation with cor triatriatum sinister under intracardiac echocardiography guidance: a case report - Zhang, Hong Cai; Yang, Bing xia; Nie, Qian; Zhao, Jue; Han, Ming Jun; Zhang, De Lai; Xie, Wen (Frontiers in Cardiovascular Medicine, 2025)
This case report describes the treatment of a 76-year-old male patient diagnosed with persistent atrial fibrillation (AF) and cor triatriatum sinister (CTS). The patient presented with palpitations and shortness of breath for four years, exacerbated over two weeks. Cardiac ultrasound and computed tomography angiography (CTA) confirmed Bank II type complete CTS, with all four pulmonary veins draining into an accessory atrium. The patient also had lacunar stroke and heart failure, with a CHA2DS2-VASc score of 5 and HAS-BLED score of 2, indicating high stroke risk and moderate bleeding risk. Given the anatomical abnormalities and clinical characteristics, we performed a one-stop procedure under intracardiac echocardiography (ICE) guidance, combining AF radiofrequency ablation and left atrial appendage closure (LAAC). Post-procedure recovery was uneventful, and follow-up transesophageal echocardiography showed no residual shunt or thrombus around the occluder. An antithrombotic regimen of rivaroxaban 15 mg once daily for three months followed by aspirin 100 mg once daily long-term was prescribed. This case highlights the critical role of ICE technology in complex cardiac anatomy and the importance of personalized antithrombotic strategies in high-risk AF patients.